(untitled) (Universal International Scientific Journal, 2026)
The article is devoted to the relevance of organizing independent learning of students in a digital learning environment. Digital learning environments provide teachers and students with a powerful set of tools and resources to support and improve the learning process. Using these technologies, teachers can create interesting and effective learning experiences that meet the needs and interests of a variety of students.